Overcoming Barriers to Livability for All Ages: Inclusivity Is the Key - Zhang, Xue (2019)
The rapid pace of population aging in cities around the world demands that planners design communities that are livable for people of all ages and abilities. In 2017, to assess progress toward this end, AARP and the International Division of the American Planning Association conducted a global survey of planners on their efforts to incorporate a livable-communityfor-all-ages approach into their work. The survey of 559 planners measured motivators, barriers, strategies for engagement and practices facilitating planners’ work on livable communities for all ages (LCA). Using the international survey, we analyze factors driving local governments’ actions to advance LCA, and factors driving outcomes incorporating a livablecommunity-for-all-ages approach in planning practices. We show how these differ between the US and non-US respondents, including how US suburbs and rural areas lag in actions toward LCA. Regression results show that local motivations such as awareness of substantial growth in older populations is a primary factor motivating local governments to take more actions. While physical design is a critical part of the solution, we find that facilitating practices and community engagement in the process are key to advancing planning for age-friendly communities. Additionally, communities that practice more traditional approaches to planning and have limited resources actually exhibit a higher level of LCA outcomes. This suggests that focusing on community engagement and facilitating practices could be a promising approach to incorporating an all age lens in planning practices.